MICROSPORE-DERIVED EMBRYOS IN BRASSICA - THE SIGNIFICANCE OF DIVISION SYMMETRY IN POLLEN MITOSIS-I TO EMBRYOGENIC DEVELOPMENT - Zaki, M; Dickinson, H (1991)
An attempt has been made to manipulate the cytological processes regulating the switch from gametophytic to sporophytic development induced by culturing the microspores of higher plants. Previous studies have indicated that sporophytic development, which leads to the formation of haploid embryos, normally follows the symmetrical division of the microspore rather than the asymmetric mitosis characteristic of normal development. To determine whether symmetry of division is a key factor in the determination of subsequent development, cells were supplied with the antimicrotubule drug colchicine to disrupt elements of the microtubular cytoskeleton believed to be involved in nuclear positioning. The treatment resulted in a highly significant increase in the numbers of cells turning to sporophytic development; further, timed applications indicated that the cells were sensitive to the drug over a 12-h period immediately prior to pollen mitosis. The results suggest that alteration of division symmetry is sufficient to switch the developmental pathway from gametophytic to sporophytic. These findings are discussed in the perspective of current models proposed for the regulation of development in eukaryotic cells. © 1991 Springer-Verlag.